Biomarkers associated with metastasis of lung cancer to brain predict patient survival. (26th May 2011) - Nasser, Sara; Ranade, Aarati R.; Sridhar, Shravan; Haney, Lisa; Korn, Ronald; Gotway, Michael; Weiss, Glen; Kim, Seungchan
MicroRNAs influence cell physiology; alteration in miRNA regulation can be implicated in carcinogenesis and disease progression. Generally, one miRNA is predicted to regulate several hundred genes, and as a result, miRNAs could serve as a better classifier than gene expression. We combine validated miRNA expression values with imaging features to classify NSCLC brain mets from non-brain mets and identify possible biomarkers of brain mets. This research involves comprehensive miRNA expression profiling, evaluation of normalisation techniques and combination of miRNA with imaging features FDG-PET/CT and CT Scan. The biomarkers were validated on an independent data set to predict potential brain mets.